An amino acid based system for CO2 capture and catalytic utilization to produce formates. Issue 17 (24th March 2021) - Wei, Duo; Junge, Henrik; Beller, Matthias
Abstract : A novel amino acid based reaction system for CO2 capture and utilization (CCU) to produce formates is presented applying a ruthenium-based catalyst. Noteworthy, CO2 can be captured from ambient air and converted to formates in one-pot (TON > 50 000). Abstract : Herein, we report a novel amino acid based reaction system for CO2 capture and utilization (CCU) to produce formates in the presence of the naturally occurring amino acid l -lysine. Utilizing a specific ruthenium-based catalyst system, hydrogenation of absorbed carbon dioxide occurs with high activity and excellent productivity. Noteworthy, following the CCU concept, CO2 can be captured from ambient air in the form of carbamates and converted directly to formates in one-pot (TON > 50 000). This protocol opens new potential for transforming captured CO2 from ambient air to C1-related products.